Toronto painting '84. - Burnett, David; Medland, C.E.; Withrow, William J.; Glembow Museum, Calgary; Beaverbrook Art Gallery, Frederiction (Toronto : Art Gallery of Ontario, 1984)
Bolduc, David ; Brown, John ; Burnett, Brian ; Coughtry, Graham ; De Guerre, Marc ; Donoghue, Lynn ; Drapell, Joseph ; Evans, Ric ; Fabo, Andy ; Girling, Oliver ; Goldstein, Sybil ; Hutner, Paul ; Johnson, Rae ; Kirton, Douglas ; Klunder, Harold ; Lyons, Jamie ; MacTavish, Catharine ; Martin, Ron ; Meigs, Sandra ; Parsons, Bruce ; Patton, Andy ; Poldaas, Jaan ; Rayner, Gordon ; Scott, John ; Simkins, Howard ; Tangredi, Vincent ; Tod, Joanne ; Van Halm, Renée ; Wieland, Joyce ; Wiitasalo, Shirley ; Youds, Robert ; Yudelman, John
biog. [1 p.], bibliog. [1 p.]
Toronto painting '84, Art Gallery of Ontario, Toronto, September 7 - October 28, 1984 ; Glembow Museum, Calgary, June 7 - July 21, 1985 ; Beaverbrook Art Gallery, Frederiction, August 15 - September 15, 1985, etc.
English
kunstcatalogus
Keywords: Canada